Latin America Asthma Epidemiology and Related Risk Factors - Aguirre-Camposano, V (Springer International Publishing, 2020)
Asthma is the most common chronic disease in children. Its high heterogeneity makes it a very complex disease, wherein several risk factors and the genetic predisposition of the patient interact to express the disease in a variable way. During the past years an important increase in the prevalence of this disease has been observed, as well as for other allergic diseases such as allergic rhinitis, rhinoconjunctivitis, food allergy, and eczema. The most important investigation in relation to asthma prevalence in children is the International Study of Asthma and Allergies in Childhood (ISAAC), where the same questionnaire was administered to children from 6 to 7 years old or adolescents from 13 to 14 years old, in diverse education centers worldwide. Although many risk and protection factors have been recognized, there is a great degree of variability in Latin America, which makes it difficult to place highly effective preventive measures. © Springer Nature Switzerland AG 2020.